Method for Improving RadViz's Navigation Function Based on Focusing and Filtering - Han, Hyunwoo; Yoon, Taerin; Ha, Hyoji; Hong, Juwon; Lee, Kyungwon (2018 IEEE 8th Symposium on Large Data Analysis and Visualization, LDAV 2018, 2018)
For user to analyze large data set with various attributes as desired, rearranging data based on purpose is vital. This study proposes a method to navigate data with a desired purpose of user by improving RadViz visualization through focusing and filtering. To help understand visualization, user studies were conducted using the music data of Spotify. As a result, our system is discovered to be effective at classifying large data set of music with attributes and navigating desired music efficiently.
Keywords: Information visualization; Large datasets; Music data; Navigation functions; RadViz; User study; Information Visualization; Multi-Task classification; RadViz